Effect of transition metals (Mn, Co, Ni, and Zn) in size-controlled metal ferrite nanocrystals on the electrocatalytic oxygen evolution reaction - Jeyavani, Vijayakrishnan; Manoj, Shanmugasundaram; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2024)
Metal ferrite (MFO) M2+Fe2O4 (M2+ = Mn, Co, Ni, and Zn) nanocrystals (NCs) with a controlled size of similar to 4 nm were synthesized using stearic acid as the capping agent via a facile solvothermal method. The as-synthesized MnFe2O4 (MnFO), CoFe2O4 (CoFO), NiFe2O4 (NiFO), and ZnFe2O4 (ZnFO) NCs were characterized by XRD, FT-IR, Raman, XPS, TGA, TEM, and HRTEM analyses. The electrocatalytic oxygen evolution reaction (OER) is significant for future renewable energy to produce pure hydrogen (H-2) fuels through H2O splitting. However, because of the complex proton-coupled multielectron transfer process, it is kinetically quite challenging. Fe-containing transition metal-based electrocatalysts are well studied since it has been observed that Fe has a significant role in enhancing OER activity. It is well-known that the size and shape of the Fe/ferrite-based nanoelectrocatalyst play a vital role in electrocatalysis reactions. However, it is also critical to understand the effect of other earth-abundant and cost-effective transition metal ions (e.g., Mn, Co, Ni, and Zn) combined with Fe/ferrite NC-based OER electrocatalytic reactions while keeping the size of NCs constant and compare their electrocatalytic properties toward the development of advanced nanoelectrocatalysts, which is rarely studied to the best of the authors knowledge. Therefore, herein, the electrocatalytic properties for OER were examined by using the as-synthesized MnFO, CoFO, NiFO, and ZnFO NCs to understand the effect of metal ions (Mn, Co, Ni, and Zn) on the Fe-based nanoelectrocatalysts by keeping the size of the nanoelectrocatalysts constant at similar to 4 nm. Additionally, the influence of different substrates, e.g., carbon paper (CP) and nickel foam (NF), on the electrocatalytic activity of MFO (MnFO, CoFO, NiFO, and ZnFO) NCs was also compared. Interestingly, as an OER nanoelectrocatalyst, the CoFO NCs on the CP substrate show better electrochemical OER activity than other MFO NCs, with a Tafel slope value of 49.4 mV dec(-1), an ECSA of 112 cm(2), and a long-term stability of 24 h, which is comparatively higher than the other as-synthesized MFO NCs. On the other hand, MnFO NCs on the NF substrate show better electrochemical OER activity than the other as-synthesized MFO NCs. Therefore, this work highlights the effect of the substrate and the influence of transition metals, e.g., Mn, Co, Ni, and Zn, on size-controlled Fe-based nanoelectrocatalysts toward developing advanced OER electrocatalysts.
Keywords: Carbonpaper; electrocatalysis; Ferrites; Nickel foam; Oxygen Evolution Reaction; Size-controlled nanocrystals